Russian export: results and trends in the context of sanctions - A. V. Salnikova (Вестник университета, 2025)
The article examines Russian export under the conditions of sanctions pressure, which is necessary in order to update existing measures and tools for its development and creation of the new ones. Based on the analysis of statistical data for 2022–2023, dynamics of the main export indicators is estimated, key results and trends in the development of the domestic export are highlighted. It has been established that these are ambiguous impact of the sanctions, transition to a non-resource export model, orientation of raw materials and non-resource exports to friendly and (or) neutral countries. It is determined that under the sanctions pressure, the Russian export has a wide potential, which can be most quickly and effectively disclosed with active and updated state support. Problematic issues of export transformation are noted: lack of a developed transport and logistics infrastructure, full-scale assistance to exporters in new markets, insufficient assistance to small and medium-sized enterprises in the export sector. As recommendations, it is proposed to stimulate the entry of Russian companies into the world markets of high value-added goods, continue increasing the share of non-primary non-energy export, expand the geography of supplies to friendly and (or) neutral countries while diversifying the commodity structure of the export.